Effects of feedback type and personality on 2,000-m ergometer performance in female varsity collegiate rowers - Stine, K. A.; Moxey, J. R.; Gilbertson, N. M.; Malin, S. K.; Weltman, A. L. (The Journal of Strength and Conditioning Research, 2019)
Rowing performance is routinely tested on ergometers, involving visual cues and verbal encouragement, whereas on-water rowing lacks the visual cues. Personality is also hypothesized to influence rowing performance. The purpose was to examine the effects of visual and verbal feedback and to determine the impact of personality on performance. Thirty-eight female collegiate rowers (body mass 75.0 ± 5.7 kg and height 176.6 ± 5.0 cm) were recruited. Participants were asked to complete a progressive continuous graded exercise test, body composition analysis, personality questionnaire (Neo five-factor inventory, version 3), and 2 randomly ordered 2000-m ergometer tests: routine verbal and visual vs. verbal only. Differences between the 2,000-m tests were analyzed with a paired t-test. The relationships among 2max">VO2max, body composition, and 2,000-m performance were analyzed with Pearson's Correlations. A 2 × 2 analysis of variance analyzed neuroticism, openness, agreeableness, and conscientiousness to investigate how personality impacted 2,000-m performance. Statistical significance was set to p = 0.05. The combination of visual plus verbal feedback trended toward improving performance compared with the verbal feedback alone (430.3 ± 8.6, 431.6 ± 8.9 seconds, respectively). High neuroticism negatively impacted 2,000-m performance (p = 0.05). Conscientiousness and agreeableness trended toward improved performance: as conscientiousness and agreeableness increase, time decreases. We conclude that the combination of verbal plus visual feedback tends to yield better 2,000-m performance and that highly conscientious, highly agreeable, and low neurotic athletes outperform their respective counterparts. Using visual plus verbal encouragement while simultaneously targeting personality factors may be a novel strategy to optimize rowers' training.